(untitled) (Música Hodie, 2013)
Commissioned by the Kronos Quartet in 1988, Zorn’s string quartet Cat O’ Nine Tails originated as a “filecard composition”, but was eventually assembled as a conventionally notated score. Subtitled “Tex Avery directs the Marquis de Sade,” the fifteen-minute work combines a variety of musical quotes, stylistic allusions, improvisational episodes, and noise elements in a frenetic and dramatic musical collage. A continuous play of fragmented and disjunctive referentiality, Cat O Nine Tails exemplifies late twentieth century postmodernism. This paper provides an analysis of the musical structure of Cat O’ Nine Tails. By applying music theorist Jonathan D. Kramer’s hierarchy of linearity and nonlinearity as an analytical model, I attempt to address Zorn’s idiosyncratic approach to time and context, and discuss how the composer simultaneously disrupts and maintains structural integrity and compositional intent. Keywords: John Zorn; Cat O’ Nine Tails; Music for string quartet; Jonathan D. Kramer; Postmodernism in music; Moment form.